Virtual reality classroom and inclusive leadership: Enhancing access for students with disabilities in secondary schools in Benue State, Nigeria - Onwughai, Juliana Omobolanle; Attah, Esther Onoja; Okpe, Michael Adole; IYALA, Felix Emeka; PETER, Joy Abosede (Journal of Interdisciplinary Studies in Education, 2026)
This study examined the role of virtual reality (VR) classrooms and inclusive leadership practices in enhancing access to learning for students with disabilities in secondary schools in Benue State, Nigeria. A descriptive survey design was adopted using 120 respondents comprising principals, vice-principals, teachers, and education officers from six public secondary schools. Data were collected using Virtual Reality and Inclusive Leadership in Education Questionnaire (VRILEQ) with a reliability coefficient of 0.84. Descriptive statistics, t-test, Pearson correlation, and regression analysis were used for data analysis. Findings revealed that inclusive leadership practices significantly supported VR integration and improved learning outcomes for students with disabilities. The study recommends improved digital infrastructure, teacher training, and leadership support for inclusive technology integration.